INTERNATIONAL THEATRICAL EDUCATIONAL PROGRAM: 25 YEARS OF EXPERIENCE IN MOSCOW ART THEATRE SCHOOL - E. V. Burdenko; I. I. Artsis; N. S. Il'yushchenko (Высшее образование в России)
The paper highlights the 25-year experience ofthe implementation ofthe international theatrical educational program "Moscow Art Theatre Semester" organized by the Moscow Art Theatre School together with the Eugene O'Neill Theatre Centre. The program should be regarded as one of the longest continual cultural and educational exchanges between the U.S. and Russia. The authors dwell on the history of its creation and on the related parts, which enable foreign students to achieve full development of professional knowledge and skills. The Moscow Art Theatre Semester immerses students-actors in the Stanislavski training method. Daily movement and acting classes are complemented with design, voice, Russian language, and Russian theater history. In addition to a conservatory-based training regimen - six days a week taught by masters at one of the world's most renowned theater companies - students experience the rich theatrical culture by attending performances of theater, opera, ballet, and music throughout the semester as well as enjoying frequent museum visits. The results of the program implementation confirm the necessity of carrying out international theatrical educational programs which is facilitated by the ongoing growth of global student mobility.